Water Valuation and Weaponization - Tetiana Gardashuk (Etikk i Praksis: Nordic Journal of Applied Ethics)
The article discovers the multiple values of water as a key element of the Biosphere and a vital natural resource that sustains the equilibrium of the global ecosystem and human well-being. Different approaches to classifying and justifying values and various interpretations of the concepts of intrinsic, instrumental, and relational values in the context of the valuation of water are considered. Values are important for the efficient sustaining, management, and protection of water and water-related ecosystems globally and locally, and just access to water resources. Understanding the role of values and their respect or neglect is crucial in times of crisis, wars, and other conflicts that affect water. By accepting the consensus about three main classes of values (intrinsic, instrumental, and relational), water weaponization, and referring to some facts of the current Russo-Ukrainian war, it is shown that military actions exacerbate most of the challenges to environmental sustainability and human life. War also aggravates the conflict between water values. Water weaponization is considered one of the forms of instrumentalization of water that has multifaceted negative impacts on the environment, human rights to water, and human welfare. It is concluded that the way to reduce the negative environmental, economic, social, humanitarian, and cultural consequences of the weaponization of water is to stop the Russian aggression in Ukraine as soon as possible.